PENGARUH PENGGUNAAN BAHASA ASING TERHADAP KOMUNIKASI GEN Z - Ayu Azumi; Dhea Amelia; Ra'abiatuladawiyah Ra'abiatuladawiyah; Salma Habina Pratiwi; Yuni Zahara (CV. Denasya Smart Publisher, 2026)
This study aims to analyze the influence of foreign language use on Generation Z’s communication patterns in various interaction contexts, including education, social relationships, and digital media. Generation Z is widely exposed to globalization and technological advancement, making the use of foreign languages particularly English increasingly common in daily conversations. This phenomenon is not only related to linguistic ability but also affects social identity, communication styles, and interpersonal perceptions. This study uses a descriptive qualitative approach through in-depth interviews, observation, and documentation involving informants aged 17–25. The findings indicate that foreign language use influences Generation Z’s communication in three major aspects: (1) increased linguistic flexibility and creativity, (2) social relationship dynamics shaped by differences in language competence, and (3) the emergence of hybrid communication styles combining local and foreign languages. These findings highlight the transformation of communication prompted by linguistic globalization within the everyday lives of Generation Z.